Key Factors Shaping Millennials' Decisions to Choose Sharia Mortgage Financing - Sufa, Faila; Nursanita, Nursanita (Lembaga Penelitian Universitas YARSI, 2025)
This study examines the factors influencing millennials' decisions to take Sharia mortgages. It employs causal hypothesis testing with a quantitative approach, using multiple linear regression analysis via SPSS Statistics 25. The population includes DKI Jakarta residents aged 20-40 years with income or employment. A sample size of 100 respondents was determined using the Slovin formula based on the Nine Targeted Samples Method. Primary data were collected through online questionnaires distributed via Google Forms. The study findings reveal that house prices positively and significantly affect millennials' decisions to opt for Sharia mortgages. Conversely, house location has a significant negative effect on their decisions. Additionally, promotion and religiosity both have positive and significant influences on the decision to take Sharia mortgages. The results underscore the importance of promoting the benefits and advantages of Sharia mortgages, particularly highlighting their differences from conventional mortgages. The implications of these findings suggest that stakeholders should provide clear, accessible, and educational information to help millennials understand the unique features of Sharia mortgages. By addressing pricing, location concerns, and promotional efforts while aligning with religious values, organizations can better cater to the preferences of this demographic, ultimately increasing the adoption of Sharia-compliant financial products.